Numerical assessment of liquid filled container subjected to free fall on rigid steel plate - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Chemicals can be a great threat to society and the environment, despite its wide usage in industrial applications. Extra precautions have to be taken into account, moreover with increasing number of accident cases involving chemical-transporting tanks. Precautions should be taken especially when transporting chemicals of radioactive nature. Should any spill of such chemicals occur, its effects on the environment and human life can be catastrophic. In tenns of passive safety, the tank designer has to study the probable effect on the tank body should the transporter get involved in a crash, thus enhancing the design. Instead of conducting real experiments or tests which requires huge sums of money, computer simulation is an alternative to predict the actual scene. ANSYS and LS-DYNA, two powerful software environments were used to simulate events of nonlinear phenomenon ranging from limited duration impacts, collisions and crashes to more pennanent defonnations providing an insight into behavioral patterns of matelials. To have more realistic environment, the mesh-less Smooth Particle Hydrodynamics (SPH) computation feature, provided by explicit finite element program of LSDYNA was used in the prediction of particle behavior of liquid (water) in the tank under stress. Besides, the software was used to predict the dent depth and reduction in plate thickness at impact points.